Students with Autism Spectrum Disorder and Didactic Situations Involving Mathematics: A Case Study - Viana, Elton de Andrade; Miarka, Roger [UNESP] (Springer Nature, 2019)
Autism is defined as one of the neurodevelopmental disorders, characterized by difficulties in reciprocal social communication and social interaction. Starting from the recognition of the characteristics of people with autism and the attention to how these characteristics are inserted in the process of teaching and learning mathematics, we assume as a guiding question of the study presented here: How do students with autism deal with didactic situations involving mathematics? To pursue this issue, the research was developed in a qualitative way through a case study of a seven-year-old student with autism, named here as Student A. The empirical data were produced through video records and written notes taken during activities in a public school in the city of São Paulo in the year of 2015. An analysis was performed through a triad of elements that enabled the identification of significant scenes: Student A’s individual conditions, the proposed tasks and the researchers’ observations. As a result, the study presents and discusses specific ways in which students with autism deal with didactic situations involving mathematics, which were categorized into five characteristic elements (response disposition, unconventional communication, own way of reasoning, constitution of valid resources and visual-manual scanning) and motivating elements, which in turn are resources with the potential to motivate Student A to interact with the environment. These elements, when known by mathematics teachers, can help them in the school dynamics of teaching and learning by enabling a better didactic planning that has as its cornerstone the differences presented in the classroom.
Keywords: Autism; Case study; Inclusion; Inclusive education; Special education